CRIMINALIZATION OF THE SMUGGLING OF MIGRANTS IN ACCORDANCE WITH THE UNITED NATIONS CONVENTION AGAINST TRANSNATIONAL ORGANIZED CRIME AND PROTOCOL AGAINST THE SMUGGLING OF MIGRANTS BY LAND, SEA AND AIR - Hartati, Aryani Sri (Indonesian Journal of International Law, 2013)
Smuggling of Migrants is categorized into Transnational Organized Crime due to its nature that involves more than one actor and crossing state borders. To overcome this problem, United Nations creates United Nations Convention against Transnational Organized Crimes followed by the Protocol against the Smuggling of Migrants by Land, Sea, and Air. This essay discusses about the development of the migrants smuggling as a form of transnational organized crime, the implementation of the provision of the UN Convention against Transnational Organized Crime and Protocol against the Smuggling of Migrants by Land, Sea, and Air in Indonesia, UK, and Australia and the enforcement of these provision to several illegal migrants cases.